Cover crop management and water conservation in vineyard and olive orchards - Novara, Agata; Cerda, Artemi; Barone, Ettore; Gristina, Luciano (Soil & tillage research, 2021)
[Display omitted] •Sustainability in orchard crops is an important goal for farmers and decision-makers.•Cover crops (CC) are widely accepted as sustainable crop management.•This review shows the role of CC in vineyard and olive grove in runoff and soil water.•The use of CC is a strategy can have a positive influence on water use efficiency.•More attention should be paid on CC impact on water availability. Sustainability in orchard crops is an important goal for farmers, decision-makers and consumers. The United Nations Sustainable Development Goals emphasize the importance of the soils in the Earth System to achieve sustainability and accomplish the Land Degradation Neutrality Challenge. Within the world agriculture land, olive and vineyards are within the eldest crops in the world, and they are also the ones with the highest degree of soil degradation. Cover crops (CC) are widely accepted as sustainable crop management that reduces soil and water losses, restores organic matter, increases biodiversity and fertility in degraded agriculture soils. The agriculture land must shift into a more sustainable agricultural practices for achieving soil and water conservation targets, and CC are of help, but not widely applied by farmers that usually expect subsidies. Runoff and soil water storage are two key processes that determine the crop production, plant health and sustainability. However, after four decades of use, there is not a consistent State-of-the-Art that clarifies the impact of service crops. Our review highlights, in quantitative terms, the role of CC exerted in vineyard and olive grove in runoff reduction and soil water status. Statistical differences were found between the average values of RC (7.37 % and 10.05 % for CC and conventional tillage (CT) management, respectively). For the soil water conservation, the ratio SWCCT/SWCCC is always higher than 1. Water competition was more pronounced in spring and decreased after blooming. The use of CC is a strategy can have a positive influence on water use efficiency, through the reduction of the excessive vine vigour in fertile soils or favouring the growth of roots in deeper layers. In low vigour vineyards, low fertile soils and in dry environment, the water competition should be correctly monitored to avoid negative effect in grape yields. Cover crops are a positive contribution to the agriculture sustainability, although Mediterranean ecosystems, where most of the olive oil and wine is produced should pay attention to their impact on water availability